Radon, Salinity and Elemental Concentrations of Water Sources within the Kuiseb and Cuvelai-Etosha Basin, Namibia - Ithindi, J.; Kgabi, N.; Atekwana, E.; Mathuthu, M.; Kalumbu, G.; Motsei, L.; Tshivhase, V. (Namibian Journal for Research, Science and Technology, 2018)
The absence of baseline information on radon measurements and concerns about possible consequences of long term exposure to high radon (Rn-222) concentrations and its progenies necessitated for the evaluation of radon concentrations in boreholes and households. This study thus investigated the levels of Radon gas (Rn- 222 ), salinity and elemental composition of different water sources (tap-water, boreholes and surface water) within the Kuiseb and Cuvelai-Etosha basin, in order to address the lack of scientific correlational studies on radon levels and toxic trace elements in drinking water. Radon concentrations were measured using an AlphaGRAUD PQ2000 PRO system, and the elemental composition was determined using a NexION 350D Inductively Coupled Plasma Mass Spectrometer. The findings of this study showed high (2.71 Bq/m3) Rn-222 concentrations in the Kuiseb (possibly caused by natural uranium ore deposits in the Erongo Region) compared to the 0.43 Bq/m3 average in the Cuvelai-Etosha Basin. The study also measured high salinity (63 0 /00) concentrations (linked to high Total Dissolved Solids of 25.46 g/L) in the Cuvelai waters compared to the (37 0/00) salinity (with low TDS of 3.8 g/L) in the Kuiseb, thus pointing to the geological and meteorological make up of Cuvelai i.e. Kalahari sedimentary rocks, runoff sediments, high temperature and evaporation rates, as well as alternating floods and drought (rainfall variations). The elements observed in significantly high concentrations include Ba, K, Sb, As, Cd, Cr, Cu, Mo, Ni, V, Zn and Bi in the Kuiseb, and Ca, Cl, Mg, Na, Al, Be, Br, Ce, Cs, Fe, Pb, Mn, Se, Ti in the Cuvelai-Etosha Basin. Further, the Cuvelai-Etosha proved to have more anthropogenic activities (including burning of vegetation) influencing the elemental composition, and causing deterioration of the water quality.